N-phosphinoamidinato silylene- and phosphine-borylborylene complexes - Fan, Jun (2023)
This work describes a straightforward method to synthesize a borylborylene without proceeding via the rearrangement of a diborene. An amidinato amidosilylene [LSiNMe2] (L = PhC(NtBu)2) and PMe3 were reacted with an N-phosphinoamidinato diborane 1 and KC8 to form a stable silylene-borylborylene 2 and a persistent phosphine-borylborylene 3, respectively. Compound 2 is stable as the borylene center is well stabilized by the silylene donor and boryl substituent, whereas compound 3 is unstable in solution due to labile PMe3. The latter was illustrated by reacting compound 3 with Ar'NC (Ar' = 2,6-Me2C6H3), where Ar'NC displaced PMe3 and inserted into the N-phosphinoamidinate ligand and B-B bond to form compound 4.